In vitro activity of tigecycline in combination with cefoperazone–sulbactam against multidrug-resistant Acinetobacter baumannii. (October 2015) - Liu, Bin; Bai, Yan; Liu, Youning; Di, Xiuzhen; Zhang, Xin; Wang, Rui; Wang, Jin
Abstract : Over the last decade, multidrug-resistant Acinetobacter baumannii (MDRAB) has emerged as one of the most problematic nosocomial pathogens. Empirical combination therapy has become a common practice to treat patients infected with MDRAB. In vitro interactions of tigecycline with cefoperazone–sulbactam were assessed in 72 MDRAB isolates. Minimum inhibitory concentrations (MICs) were determined by broth microdilution method. Antibiotic interactions were determined by chequerboard and time–kill assays. Chequerboard analysis showed 29·2% synergy and no antagonistic interactions. Time–kill assays confirmed the synergistic interaction between two agents for three of four selected extensively drug-resistant A. baumannii (XDRAB) isolates. No antagonism was revealed by time–kill assays. Moreover, tigecycline in combination with cefoperazone–sulbactam appeared to be more effective than tigecycline in combination with sulbactam against XDRAB. In conclusion, in vitro synergistic activities of tigecycline in combination with cefoperazone–sulbactam against MDRAB were demonstrated, suggesting a superior treatment option against MDRAB.